2020
DOI: 10.1158/1055-9965.epi-20-0358
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Population Attributable Risk Proportions Associated with Body Mass Index and Breast Density by Race/Ethnicity and Menopausal Status

Abstract: Background: Overweight/obesity and dense breasts are strong breast cancer risk factors whose prevalences vary by race/ethnicity. The breast cancer population attributable risk proportions (PARP) explained by these factors across racial/ethnic groups are unknown.Methods: We analyzed data collected from 3,786,802 mammography examinations (1,071,653 women) in the Breast Cancer Surveillance Consortium, associated with 21,253 invasive breast cancers during a median of 5.2 years follow-up. HRs for body mass index (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 60 publications
(68 reference statements)
1
34
2
Order By: Relevance
“…25 Racial/ethnic disparities in BD awareness in states such as New York where only women with dense breasts receive notification may be partly attributed to decreased prevalence of BI-RADS ascertained dense breast in these population groups and therefore lower likelihood of receiving DBN. [26][27][28][29][30] Yet, racial and ethnic differences in the proportion of women with BI-RADS ascertained dense breasts was not large in our study. Further, by accessing clinical data to ascertain personal DBN, we found that disparities in BD knowledge and awareness remained after accounting for DBN, thus reducing the possibility of differential prevalence of DBN as an explanation.…”
Section: Discussioncontrasting
confidence: 57%
“…25 Racial/ethnic disparities in BD awareness in states such as New York where only women with dense breasts receive notification may be partly attributed to decreased prevalence of BI-RADS ascertained dense breast in these population groups and therefore lower likelihood of receiving DBN. [26][27][28][29][30] Yet, racial and ethnic differences in the proportion of women with BI-RADS ascertained dense breasts was not large in our study. Further, by accessing clinical data to ascertain personal DBN, we found that disparities in BD knowledge and awareness remained after accounting for DBN, thus reducing the possibility of differential prevalence of DBN as an explanation.…”
Section: Discussioncontrasting
confidence: 57%
“…Breast cancer is the most common malignancy among women worldwide, with 1 in 8 North American women expected to be diagnosed in their lifetime [1]. While there is no single biological target for the primary prevention of breast cancer, diet, adult weight gain, and obesity are estimated to be responsible for up to 50% of cases [2][3][4][5]. Metabolic dysfunction, signified by presence of hyperglycemia, dyslipidemia, hypertension, and abdominal obesity, is primary driver in the risk of type 2 diabetes and cardiovascular diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Screening is designed to detect breast cancers earlier than would have occurred in the absence of screening so that treatment confers a benefit when applied sooner, whereas breast cancer prevention strategies can be used to avoid disease and its therapies. While lifestyle changes such as avoiding obesity or reducing alcohol intake could potentially reduce risk of developing breast cancer [65][66][67][68][69], hormonal risk-reducing drugs like tamoxifen can prevent half of ER-positive breast cancer among women with high 5-year risk of breast cancer [70]. None of the other known prevention interventions have this magnitude of effect on avoiding breast cancer.…”
Section: Challenges and Opportunities: Primary Preventionmentioning
confidence: 99%